Prenos vibracij po ukrivljenih cevovodih v prostoru - Tadina, Matej (Strojniški vestnik, 2007)
This paper briefly presents the transfer-matrix method (TMM) for the vibrationanalysis of a 3-dimensional piping system. The transfer matrix of a curved pipe with fluid was derived based on the exact solution of the governing equations, where the axial deformability was also taken into account. Only the steady-state response for the case of harmonic excitations was analyzed. With the formulation of the transfer matrix for a straight pipeand for a curved pipe, a 3-dimensional complex piping system can be easilymodeled. The inviscid fluid-dynamic forces were derived according to theplug-flow approximation and the slender-body theory.
Keywords: cevovodi; vibracije; modeliranje; metode prenosnih matrik